1974
DOI: 10.1073/pnas.71.4.1207
|View full text |Cite
|
Sign up to set email alerts
|

A Platelet-Dependent Serum Factor That Stimulates the Proliferation of Arterial Smooth Muscle Cells In Vitro

Abstract: Dialyzed serum from clotted monkey blood ("blood serum") promotes the proliferation of monkey arterial smooth muscle cells in culture, but dialyzed serum prepared from recalcified platelet-poor plasma ("plasma serum") is much less effective. Addition of platelets and calcium to platelet-poor plasma increases the activity of plasma serum to the same level achieved with blood serum. Furthermore, addition to plasma serum of a platelet-free supernatant prepared by exposing purified platelets to thrombin also stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
597
1
17

Year Published

1978
1978
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,577 publications
(628 citation statements)
references
References 13 publications
13
597
1
17
Order By: Relevance
“…This finding led researchers to conclude that insulin acts in a coordinated manner with serum components. Growth factors were discovered one after another during this era: nerve growth factor,67 epidermal growth factor,68, 69 insulin‐like growth factor,70, 71, 72, 73 fibroblast growth factor (FGF),74, 75 platelet‐derived growth factor,76, 77, 78 and transforming growth factor (TGF) 79, 80. The addition of these growth factors to a culture medium increased cellular proliferation.…”
Section: History Of Cell Culture Mediamentioning
confidence: 99%
“…This finding led researchers to conclude that insulin acts in a coordinated manner with serum components. Growth factors were discovered one after another during this era: nerve growth factor,67 epidermal growth factor,68, 69 insulin‐like growth factor,70, 71, 72, 73 fibroblast growth factor (FGF),74, 75 platelet‐derived growth factor,76, 77, 78 and transforming growth factor (TGF) 79, 80. The addition of these growth factors to a culture medium increased cellular proliferation.…”
Section: History Of Cell Culture Mediamentioning
confidence: 99%
“…PDGF has long been recognized as a powerful VSMC mitogen [3] and the induction of PDGF receptors in VSMCs during atherogenesis has been demonstrated in several studies [4,5]. Blockade of PDGF, whether by anti-PDGF antibody [6][7][8], PDGF receptor antisense therapy [9,10], or chimeric knockout in mice [11], reduces lesion formation after vascular injury.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro observation that serum contains growth-promoting activity for connective tissue cells not present in plasma (11) led to the discovery that platelets contain mitogens that are released during coagulation which stimulate the growth of 3T3 cells (12), smooth muscle cells (13), and glial cells (14). Recently, Dainiak et al (1) reported that factors released from thrombin-treated platelets and the purified platelet mitogen, PDGF, enhanced human erythropoiesis in vitro.…”
Section: Discussionmentioning
confidence: 99%